Pengembangkan Bahan Ajar Elektronik LKPD yang Terintegrasi STEM-PjBL pada Materi Termokimia di SMAN 1 Gunung Talang - Afri Dhonal; Effendi Effendi (Entalpi Pendidikan Kimia, 2021)
The collaboration between STEM and PjBL is able to increase interest, motivation, creativity, and effectiveness, and is able to influence the development of students' attitudes in learning. This study produces electronic student worksheets that are integrated with STEM-PBjL, then reveals its validity and practicality. This research is an R&D (Research and Development) research and a 4-D model which includes: (1) define, (2) design, (3) develop, (4) deseminate. The electronic validation of student worksheets was carried out by 3 Chemistry lecturers of FMIPA UNP and 2 Chemistry teachers and a practical test with 2 teachers and 17 students of Class XII SMA Negeri01 Gunung Talang. Analysis of the validity test used Aiken's V with the validation results of 0.884 and the practicality of using Kappa Kohen with the results, namely for the practicality test of teachers and participants with results of 0.693 and 0.758 which were in high categories. The results of the data show that the electronic student worksheets are valid and practical to use. Kolaborasi antara STEM dan PjBL mampu meningkatkan ketertarikan, motivasi, kreatifitas, dan efektifitas serta mampu mempengaruhi pengembangan sikap peserta didik dalam pembelajaran. Penelitian ini menghasilkan elektronik LKPD yang terintegrasi STEM-PjBL, kemudian mengungkapkan validitas dan praktikalitasnya. Penelitian ini merupakan penelitian R&D (Research and Development) dan model 4-D yang meliputi: (1) define, (2) design, (3) develop, (4) disseminate. Validasi elektronik LKPD ini dilakukan 3 dosen Kimia FMIPA Universitas Negeri Padang dan 2 orang guru Kimia SMA dan uji praktikalitas dengan 2 orang guru dan 17 orang siswa Kelas XI SMA Negeri 1 Gunung Talang. Analisa uji validitas mengunakan Aiken’s V dengan hasil validasi yaitu 0.884 serta praktikalitas mengunakan Kappa Kohen dengan hasil yaitu untuk uji praktikalitas guru dan peserta dengan hasil yaitu 0.693 dan0.758 memiliki kategori tinggi. Hasil data menunjukkan bahwa elektronik LKPD valid dan praktis digunakan.